STRATEGI BAURAN PEMASARAN DAN EFISIENSI SALURAN DISTRIBUSI HOME INDUSTRI MARNING JAGUNG DI KECAMATAN KALIANGET - Putri Ulandari; Dody Tri Kurniawan; Fatmawati Fatmawati (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2022)
Corn is an agricultural commodity that is quite potential to be developed due to various factors, apart from being a food ingredient, corn also contains a lot of carbohydrates second after rice and corn is also used as an ingredient in the animal feed industry. In addition to being animal feed, corn can also be processed into a product that has a high added value for the corn itself, one of which is made into processed corn marning which has a distinctive taste. The corn marning produced by UD Ajum Pertama is located in Kalianget Timur Village, this corn marning business was initiated in the 90s which was later developed into one of the home corn marning industries which is quite liked by the people of Sumenep. The success of a home industry will not escape the problems that exist, so that these problems result in delays in the process of production activities. The problems experienced by UD Ajum Pertama include a lack of understanding about marketing competition for corn marning products. So the opportunity to enter the world of marketing is very minimal. The results of the analysis show that marketing in the production of marning corn at UD Ajum Pertama has met the Marketing Mix aspect, namely the 4P (product, price, place, promotion) namely the product, namely in the form of marning corn, the price (price), namely there are various price options, place (place), namely there are 4 different places, promotion (promotion), namely for the promotion aspect, producers still promote their products directly to consumers. For the marketing channel process in UD Ajum Pertama maize marning is currently quite developed, there are 3 marketing channels, each of which has its own efficiency value, for the most efficient marketing channel is channel 1.